Soluble expression and purification of the functional interleukin-30 protein in Escherichia coli. Issue 6 (17th August 2016) - Zhang, Jun; Liu, Xiao; Huang, Nongyu; Hu, Zhonglan; Wu, Wenling; Teng, Xiu; Wang, Zhen; Wei, Xiaoqiong; Tang, Huan; Wu, Xueping; Chen, Zhenyu; Li, Jiong; et al.
ABSTRACT: Interleukin-30 (IL-30), or IL-27p28, is the α subunit of IL-27 constructed by Epstein–Barr virus-induced gene 3 (EBI3) and IL-27p28 binding via noncovalent bonds. IL-30 can be independently secreted and function independently of IL-27. Recent studies demonstrated IL-30 could concurrently antagonize T helper 1 (Th1) and Th17 responses and might have therapeutic implications for controlling autoimmune diseases. However, no reports have stated an efficient method to generate a relatively large quantity of IL-30. In this study, an Escherichia coli expression system for the rapid expression of the mouse IL-30 is developed. For the first time, IL-30 was expressed in a form of soluble fusion protein and purified using a method of simple affinity chromatography. In order to avoid the impact of minor codons on expressing eukaryotic protein in E. coli and to improve the expression quantity, the nucleotide sequence of IL-30 was optimized. The optimized gene sequence was then subcloned into the pET-44a(+) vector, which allowed expression of IL-30 with a fusion tag, NusA. The vector was transformed into E. coli and the expressed fusion protein, NusA-IL-30, was purified by Ni chromatography. Then the fusion tag was removed by cleavage with thrombin. The purity of purified IL-30 was identified using sodium dodecyl sulfate polyacrylamide gel electrophoresis (SDS-PAGE) as well as high-performance liquid chromatography (HPLC) and the purity was up to about 92%. The yield of IL-30 was 8.95 mg from 1 L of bacterial culture. Western blot confirmed the identity of the purified protein. The recombinant IL-30 showed its biological activity by inhibiting Th17 differentiating from naive CD4 + T cells. Therefore, this method of express and purifying IL-30 provides novel procedures to facilitate structural and functions studies of IL-30.